IMPLEMENTATION OF INTERNATIONAL PUBLIC SECTOR ACCOUNTING STANDARDS - Shanasirova Nodira Abdullaevna,; Tulovov Erkinjon Toʻlqin oʻgʻli , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article addresses the issues of implementing International Public Sector Accounting Standards (IPSAS) as an important tool for enhancing transparency, accountability, and efficiency in the management of public finances. The objectives and benefits of IPSAS are discussed, including improving the quality of financial reporting, attracting investment, and increasing trust in government institutions. Special attention is given to the process of adapting the standards in Uzbekistan, including the development of national standards, training specialists, modernizing technologies, and providing legal and regulatory support. The challenges associated with the implementation of IPSAS are also analyzed, along with the prospects for their application in fostering sustainable economic development.